Analysing optimum and alternative farm plans for risk averse grain crop farmers in Kaduna state, northern Nigeria - Olarinde, L.O.; Manyong, Victor M.; Okoruwa, V.O. (2008)
It has been argued that the limited success of Nigeria in rural development programmes could be due to absence of a prior analysis of attitudes towards, risk inherent in traditional agriculture. This paper was therefore conceived to explain farmers’ cropping patterns vis-à-vis their attitudes towards risk. The paper applied an analytical procedure that made use of the conventional linear programming, and the Target Minimization of total absolute deviations (Target MOTAD) as the major tools. Results indicate that farmers’ existing and profit maximizing crop plans are risk inefficient. They also show that there are increasing levels of risks of the farm plans as the farm size decreases. Sustainable farm plans that minimize risk and can ensure desirable returns (gross margins) are suggested for the three identified categories of farers that were surveyed for the analysis. The study provides a critical methodological framework that can help understand the alternative ways in which these farmers actually manage risk, particularly in a complex and unstable economic environment such as Nigeria.